Experimental investigation of anion–π interactions – applications and biochemical relevance. Issue 9 (23rd December 2015) - Giese, M.; Albrecht, M.; Rissanen, K.
Abstract : Anion–π interactions, intuitively repulsive forces, turned from controversial to a well-established non-covalent interaction over the past quarter of a century. Abstract : Anion–π interactions, intuitively repulsive forces, turned from controversial to a well-established non-covalent interaction over the past quarter of a century. Within this time frame the question "Anion–π interactions. Do they exist?" could be answered and even more importantly its functional relevance was proven. The present feature article summarizes the experimental findings of anion–π studies in the gas phase, solution and in the solid state and highlights the application of anion–π interactions in anion recognition, sensing and transport as well as in catalysis. Moreover, the biochemical relevance of this weak intermolecular force is comprehensively reviewed.